About the problem of time in human reality in the thought of Zubiri - Espinoza Lolas, Ricardo A. (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
What we are investigating in this article is the great importance of the theme of time in relation to human reality according to the thought of Zubiri. One has to say radically that intelligence is «temporal». Intelligence is sentient and it senses things as real. Intelligence feels and it feels things as real. Thus, it feels them as merely being in the world. It is the essence of reality. While sensing things as being in the world, intelligence senses them as temporary, because one is temporarily in this world. This is the mode of being; time is radically the mode of being. Man senses temporarily and therefore his sensing is lasting and projecting; intelligence structurally lasts and projects only because one «intellectively knows temporarily».
Keywords: time; consciousness; duration; projection; history